Running-in as an Engineering Optimization - Jamari, Jamari (J@ti Undip : Jurnal Teknik Industri, 2007)
Running-in is a process which can be found in daily lives. This phenomenon occurs after the start of the contact between fresh solid surfaces, resulting in changes in the surface topography, friction and wear. Before the contacting engineering solid surfaces reach a steady-state operation situation this running-n enhances the contact performance. Running-in is very complex and is a vast problem area. A lot of variable occurs in the running-in process, physically, mechanically or chemically. These transient phenomena should be optimized so that it is beneficial. In this paper the global analysis of running-in in term of engineering optimization is presented.Â  Literature that reports of what have been published about knowledge and ideas, on the running-in topic by accredited scholars and researchers, are reviewed. The running-in model which can predict the real engineering surfaces in its operation is proposed. Key words: optimization, running-in, elastic-plastic contact, friction, wear,